DESIGNING A STUDENT SCIENTIFIC CLUB IN THE EDUCATIONAL SPACE OF A SPORTS UNIVERSITY - Fokin A.M. ,; Saykina E.G. ,; Kostov F.F. ,; Ovchinnikova A.V. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to substantiate the creation of a student scientific club "ON START" on the basis of self-government at the Institute of Physical Culture and Sports and substantiate the effectiveness of its functioning. Results and conclusions. The role of creating a student scientific club on the basis of self-government for the formation of an asset of studying youth, with the aim of uniting them and attracting new members to carry out research activities, is substantiated. Based on the results of a survey of students of the Institute of Physical Culture and Sports, a plan of scientific events was developed, technologies for their promotion were presented to involve them in research activities and increase interest in it. The effectiveness of the work of the scientific student club is substantiated, the quantitative increase in the indicators of club members is presented. The ways of attracting students to scientific work are determined.